Teachers’ Challenges in Research Engagement: Basis for a Proposed Technical Assistance Plan - Lea Vergara; Evelyn Sublay (JPAIR)
This study aimed to investigate the factors teachers perceived as the challenges in their research engagement. A total of sixty (60) teacher-respondents were included in this study. Forty-five (45) teachers participated in the survey, while the other fifteen (15) participated in the in-depth interview. The research also utilized an exploratory sequential mixed-method design to sustain triangulation. Based on the findings, three (3) superordinate themes emerged from the qualitative data, which include: (1) Limitations in Teachers’ Time and Workloads; (2) Unsupportive School Culture and Teachers’ Attitude toward Research; and (3) Teachers’ Limited Research Knowledge and Skills. The survey reveals that teachers face challenges in research engagement due to heavy workloads, lack of support, limited knowledge of the research process, lack of confidence, fear of rejection, and insufficient skills in crafting titles, research questions, reading research works, and preparing references using various citation styles. The most important finding of this study is that it demonstrates how education is altering its perceptions about research. Educators concur that education research is crucial, particularly in enhancing the provision of basic educational services. Teachers were deterred from conducting research despite their willingness due to several factors. For successful engagement of teachers in research, all identified factors preventing them from research engagement must be addressed properly